2009
DOI: 10.1007/s00122-009-0994-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL underlying isoflavone contents in soybean seeds among multiple environments

Abstract: Soybean isoflavones are valued in certain medicines, cosmetics, foods and feeds. Selection for high-isoflavone content in seeds along with agronomic traits is a goal of many soybean breeders. The aim of the study was to identify the quantitative trait loci (QTL) underlying seed isoflavone content in soybean among seven environments in China. A cross was made between 'Zhongdou 27', a soybean cultivar with higher mean isoflavone content in the seven environments (daidzein, DZ, 1,865 microg g(-1); genistein, GT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 36 publications
9
94
1
2
Order By: Relevance
“…Previous reports (Meksem et al 2001, Kassem et al 2004, Primomo et al 2005, Kassem et al 2006, Zeng et al 2009) have identified QTLs that control the content of daidzein derivatives on linkage groups (LG, hereafter) A1, F, H, I, K, M and N. QTLs controlling the content of genistein derivatives have been identified on LG-A2, C2, F, G, H and M. QTLs controlling the content of glycitein derivatives have been identified on LG-B1, D1a, F, G, H, I, J, M, N and O. In addition, several QTLs that regulate the total isoflavone content as well as the content of all isoflavone groups have been identified.…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports (Meksem et al 2001, Kassem et al 2004, Primomo et al 2005, Kassem et al 2006, Zeng et al 2009) have identified QTLs that control the content of daidzein derivatives on linkage groups (LG, hereafter) A1, F, H, I, K, M and N. QTLs controlling the content of genistein derivatives have been identified on LG-A2, C2, F, G, H and M. QTLs controlling the content of glycitein derivatives have been identified on LG-B1, D1a, F, G, H, I, J, M, N and O. In addition, several QTLs that regulate the total isoflavone content as well as the content of all isoflavone groups have been identified.…”
Section: Introductionmentioning
confidence: 98%
“…The control of isoflavone content in soybean seeds is largely genetic rather than the environmental interactions (Gutierrez-Gonzalez et al, 2009;Hoeck, Fehr, Murphy, & Welke, 2000;Murphy et al, 2009), and several minor effects QTL have been found which determined amounts of isoflavonein soybean. Numerous studies have shown soybean isoflavones to be a quantitatively inherited trait (Kassem et al, 2004;Meksem et al, 2001;Kassem et al, 2006;Zeng et al, 2009). Identification and mapping isoflavones QTL could offer breeders improving the level of isoflavones in soybean through marker assisted selection (MAS).…”
mentioning
confidence: 99%
“…Another high density genetic linkage maps was constructed using the 1,536 Universal Soy Linkage Panel 1.0 SNP markers in the 'PI 438489B' by 'Hamilton' populations and 31 linkage groups were obtained and used in this study . Up to date several isoflavones QTL were identified from the linkage map constructed by different markers (Kassem et al, 2004;Gutierrez-Gonzalez et al, 2009;Zeng et al, 2009;Gutierrez-Gonzalez et al, 2010). SNP markers allow the anchoring of genetic maps and QTL on the soybean genome sequence so identifying large genomic regions each containing several hundred genes.…”
mentioning
confidence: 99%
“…Furthermore, highly significant positive correlations were found between chlorogenic acid and rutin (Table 2). Previous QTL studies on main crops have frequently detected regions of the genome that contain clusters of QTLs for highly correlative traits (Zeng et al, 2009;Avia et al, 2013;Bian et al, 2013). Clusters of QTLs were also observed for growth traits and various leaf traits in poplar (Bradshaw and Stettler, 1995;Wu et al, 1997), for wood properties and growth traits in the genus Eucalyptus (Verhaegen et al, 1997;Freeman et al, 2009;Thumma et al, 2010), for growth traits in Salix (Tsarouhas et al, 2002;Ronnberg-Wastljung et al, 2005), for leaf morphological characters in European beech (Scalfi et al, 2004) and oak (Gailing, 2008;Gailing et al, 2013), and for chemical compositions in peach (Eduardo et al, 2013) and oil palm (Montoya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%